THE COMPETITIVENESS OF FUNCTIONAL FOOD PRODUCTION - Vukelić, Nataša; Živković, Jasmina; Okanović, Đorđe (Economics of Agriculture, 2013)
Raising people’s awareness about taking care of their health and development of the food industry, medicine, and those branches of science that deal with the relationship between nutrition and health has led to the popularization of the foods for which special health effects are proven. Functional foods are foods whose longer consumption can have preventive or therapeutic effects on different aspects of human health. It can be conventional with bioactive components, or "strengthened" so the risk of certain illness can be reduced. Despite increasing number of researches about functional food, there is a lack of information about psychosocial factors which influence on consumers attitudes regarding functional food. Most research related to functional food is concentrated on its possible health effects, while relatively little is known about consumers’ reaction to it. The aim of this work is to assess interest of consumers for buying functional food, according to obtained consumers attitudes. The survey has been conducted in area of Vojvodina, in cities such as Novi Sad, Subotica, Zrenjanin, Vršac, Ruma and Inđija, in the period from August 15th till September 10th, 2012. The example included 400 respondents, who were questioned with previously prepared questionnaires, mainly in supermarkets, where consumers can buy functional foods. Obtained results were analyzed in program package software SPSS 19 with use of descriptive statistics. According to the obtain results, it can be concluded that is necessary to further inform consumers about functional food and its benefits in regard to conventional food. Also, it is necessary to define market of functional food in Serbia, adopt certain regulations which can be helpful for increasing of consumers confidence about functional food and make larger consumption of this kind of food, which can result in better health condition of the nation.